2004
DOI: 10.1002/ps.889
|View full text |Cite
|
Sign up to set email alerts
|

Time effect on bentazone sorption and degradation in soil

Abstract: Previous sorption/desorption batch experiments have indicated that bentazone is weakly sorbed by soils. In addition, field experiments have shown that 4% of the bentazone sprayed can be leached to drainage water. In order to complete bentazone characterisation, we have assessed the effect of time on its behaviour in contrasting soils. In laboratory studies, bentazone was added to three topsoils (sandy, loamy and clay soils). Bentazone degradation, sorption/desorption kinetics and isotherm measurements were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 16 publications
4
23
0
Order By: Relevance
“…In general, bentazone degradation in soil follows first order kinetics , suggesting cometabolic degradation, without growth of organisms involved (Piutti et al, 2002). Soil organic matter content and pH are the soil properties that have been identified as having the greatest influence on the degradation of bentazone (Boivin et al, 2004). Contact time and soil type have a significant effect on bentazone availability (Boivin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, bentazone degradation in soil follows first order kinetics , suggesting cometabolic degradation, without growth of organisms involved (Piutti et al, 2002). Soil organic matter content and pH are the soil properties that have been identified as having the greatest influence on the degradation of bentazone (Boivin et al, 2004). Contact time and soil type have a significant effect on bentazone availability (Boivin et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic matter content and pH are the soil properties that have been identified as having the greatest influence on the degradation of bentazone (Boivin et al, 2004). Contact time and soil type have a significant effect on bentazone availability (Boivin et al, 2004). It has been observed that the rate constant for bentazone dissipation was highest in the topsoil and decreased with depth (Leistra et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Microorganisms have always been reported as mediators in both the interaction of pesticides with the soil and their degradation (Gevao & Semple, 2000;Dubus et al, 2001). The adsorption of weakly acid organic pesticides in the soil depends on the composition of the soil and its pH (Clause & Fabricius, 2002;Boivin et al, 2004;Wauchope et al, 2002), and may sometimes favor the leaching by surface and groundwater. Some studies have shown major interactions between the adsorption and degradation of pesticides (Guo et al, 2000;Gevao et al 2000), since the chemical adsorption reduces the access of microorganisms, thereby limiting the degradation and transport of these compounds (Selim et al, 1999;Koskinen et al, 2001;Moyer et al, 1972).…”
Section: Environmental Risk and The Use Of Pesticidesmentioning
confidence: 99%
“…High concentrations may be diffused in capillary spaces. Bentazon in mobile water, during its spread in soil porosity, could be subject to a quick adsorption phenomenon (Boivin et al, 2004). Despite the short contact time, a part of the initial pesticide amount would be retained on external sorption sites of the soil particles.…”
Section: Significancementioning
confidence: 99%
“…We varied the formulation and 324 S. Guimont et al application volumes of the bentazon solution. Bentazon is a herbicide, used for cereal protection, chosen in this study as a model because of its high solubility in water (Abernathy and Wax, 1973;Huber and Otto, 1994) and its weak adsorption on soil constituents (Grey et al, 1996;Boivin et al, 2004). By successive stages of percolation and centrifugations, we analysed the amounts of bentazon transferred by mass flow and the concentration spread in the immobile water compartments.…”
Section: Introductionmentioning
confidence: 99%